2022
DOI: 10.22503/inftars.xxii.2022.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Mentoring for Women at Universities

Abstract: Universities can affect students’ entrepreneurial ambitions positively. On the one hand, the increasing number of universities with business and management programmes reflects the growing level of entrepreneurial ambition among students. On the other hand, there are visible differences in terms of the proportion of male to female founding students. Based on the peer-mentoring method, action-based research was carried out with a sample of 20 female students aimed at examining whether and how formal mentorship c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, as Huszák and Oborni (2022) elaborate in their study, differences can be demonstrated in the proportion of male and female students founding start-ups. The action-based research of Huszák and Oborni (2022), based on the peer-mentoring method, examines whether formal mentoring can be integrated into university education and whether it encourages the entrepreneurial ambitions of female students. The research highlights the need for mentoring in influencing learning outcomes and entrepreneurship ambitions, as well as the critical conditions for integrating the mentorship approach into higher education.…”
Section: Contribution Of the Thematic Blockmentioning
confidence: 92%
See 2 more Smart Citations
“…However, as Huszák and Oborni (2022) elaborate in their study, differences can be demonstrated in the proportion of male and female students founding start-ups. The action-based research of Huszák and Oborni (2022), based on the peer-mentoring method, examines whether formal mentoring can be integrated into university education and whether it encourages the entrepreneurial ambitions of female students. The research highlights the need for mentoring in influencing learning outcomes and entrepreneurship ambitions, as well as the critical conditions for integrating the mentorship approach into higher education.…”
Section: Contribution Of the Thematic Blockmentioning
confidence: 92%
“…The impact of higher education courses and programmes on students' entrepreneurial ambitions is also a topic that has been extensively analysed in literature (Fayolle 2019). In their study published in present thematic block, Huszák and Oborni (2022) correspondingly point out that the increased number of business and management programmes in higher education institutions (Valerio et al 2014;Fayolle 2019) reflects the growing entrepreneurial ambitions of students, and that there are more and more start-ups founded by university students -not only at Stanford University but also at European HEIs (Volkmann and Audretsch 2017). However, as Huszák and Oborni (2022) elaborate in their study, differences can be demonstrated in the proportion of male and female students founding start-ups.…”
Section: Contribution Of the Thematic Blockmentioning
confidence: 99%
See 1 more Smart Citation